1978
DOI: 10.2307/3003592
|View full text |Cite
|
Sign up to set email alerts
|

The Bankruptcy Decision

Abstract: Thispaper investigates the circumstances under which a firm will be forced into bankruptcy. The model developed can be viewed as part of a largerframework which would be necessary to address the question of optimalfinancial policy in a world of taxation, bankruptcy costs, investment and depreciation, uncertainty, etc. The model focuses on the conflicts of interest among various claimants to the assets and income flows of the firm (the stockholders, bondholders, and bank lenders). We derive conditions under whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
184
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(193 citation statements)
references
References 9 publications
6
184
0
3
Order By: Relevance
“…There is a theoretical literature that indicates that firms close to bankruptcy may also be motivated to cheat their customers by reducing safety (Bulow and Shoven, 1978). These firms can reduce expenses by cutting maintenance and training, yet can declare bankruptcy to protect against claims in the event that a major crash occurs.…”
Section: Why Deregulation Might Effect Workplace Safetymentioning
confidence: 99%
“…There is a theoretical literature that indicates that firms close to bankruptcy may also be motivated to cheat their customers by reducing safety (Bulow and Shoven, 1978). These firms can reduce expenses by cutting maintenance and training, yet can declare bankruptcy to protect against claims in the event that a major crash occurs.…”
Section: Why Deregulation Might Effect Workplace Safetymentioning
confidence: 99%
“…Further studies analyse the influence of biased judges (Bris et al 2005;Baird 1986) or the quality and judicial discretion of judges on the ex post outcome of a bankruptcy procedure (Ayotte and Yun 2007;Bernhardt and Nosal 2004). Another issue discussed in the literature is the conflict of interest among multiple creditors (Blazy and Chopard 2004) or the problems due to multiple classes of creditors (Bulow and Shoven 1978;White 1989;Gertner and Scharfstein 1991). This paper addresses the individual incentives of a better-informed insolvency administrator as an additional source of filtering failure.…”
Section: Introductionmentioning
confidence: 99%
“…Granting sufficient debt forgiveness to an insolvent firm requires a high degree of coordination among creditors, and coordination is difficult to achieve when creditors are many. A number of authors have suggested that the larger the number of creditors the more difficult is debt renegotiation (Bulow and Shoven, 1978;White, 1980 and, and empirical evidence shows that firms with more layers of creditors are less likely to restructure their debts out of court . The concern about losses of firm value in financial distress has led a number of countries to introduce special bankruptcy statutes which, by weakening creditors' contractual rights, make it easier for indebted firms to obtain debt forgiveness (Mitchell, 1990).…”
Section: Introductionmentioning
confidence: 99%